Swim start performances at the Sydney 2000 Olympic Games - Cossor, J.; Mason, B. (2000)
The starting performance of finalists and semi-finalists in the swimming competition at the 2000 Olympic Games was analysed. Start times were shown to consist of between 0.8% and 26.1% of the overall race time depending on the event. The start time was then broken into various phases to determine the significance of each phase on the overall start time. It was shown that the most significant variables in determining a fast start time were the underwater distance and time for both the male and female events. However, individual differences were found for all events so coaches must take these into account when training the start phase of a race with their swimmers.